UNEARTHING T. REX: THE LAW AND ECONOMICS OF PALEONTOLOGICAL FINDS. (21st April 2020) - Hallwood, Paul; Miceli, Thomas J.
Abstract : This paper assesses the economic aspects of the search for and recovery of fossils on U.S. lands. The objective is taken to be the maximization of the social value of these resources, including the market and scientific values. Because independent searchers may not internalize the scientific value, we develop a reward scheme that incentivizes both optimal recovery of finds, and optimal search. We then trace how U.S. federal and state laws have tried to strike a balance between search activity and scientific recovery. We argue that existing law deals well with recovery but does not generally promote optimal search. ( JEL D83, H41, I23, K11, O32)